Investigating the role of framework topology and accessible active sites in silicoaluminophosphates for modulating acid-catalysis. Issue 20 (12th September 2018) - Potter, Matthew E.; Kezina, Julija; Bounds, Richard; Carravetta, Marina; Mezza, Thomas M.; Raja, Robert
Abstract : Framework topology and the acid sites significantly influence the Beckmann rearrangement, affecting the design of solid-acid catalysts. Abstract : The structure–property correlations which direct the formation of specific active-acid sites in nanoporous silicoaluminophosphates (SAPOs) have been explored, to afford a molecular basis for the rational design of solid-acid catalysts. It is demonstrated that the influence of the specific zeotype framework extends beyond modulating Brønsted acidity, with the framework topology playing a fundamental role in reaction kinetics. The structural integrity and nature of the active site has been probed using a combined catalysis and multi-technique characterization study, aimed at optimizing the production of ε-caprolactam.